Who really benefits from surgical tray reduction? - John-Baptiste, Ava (Journal of Thoracic Disease, 2018)
Cichos and colleagues (1) describe applying the process of lean to surgical trays at the University of Alabama at Birmingham Hospital. Through a consensus process, three surgeons in the Division of Cardiothoracic Surgery identified the least number of instruments required for mediastinoscopy, video-assisted thoracoscopic surgery, robotic thoracic surgery and thoracotomy, achieving reductions of 75%, 62%, 61% and 44%, respectively.